Intensity of Uret Pest Attacks and Results Sweet Potato Harvest Purpel (Ipomea batatas L.) Harvest Yields on Several Types of Mulch - Putri, Dita Dwi; Supeno, Bambang; Sudharmawan, A. A. K. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Sweet potato (Ipomoea batatas L.) is an important food commodity in Indonesia and is widely used as an alternative carbohydrate source. This study aims to determine the effect of several types of mulch on the intensity of wireworm attacks and sweet potato (Ipomoea batatas L.) yield. The research method used was an experimental field trial. The experiment was designed with RAK (Randomized Block Design), with three treatments. The treatments were without mulch (K0), black silver plastic mulch (K1), and straw mulch (K2). The results of the study found two species of wireworm pests, namely Phyllophaga sp. and Leucopholis sp. The highest attack intensity was obtained in the K2 treatment at 33.42%, followed by K1 at 28.08%, and the lowest in K0 at 23.10%, but not statistically significantly different. The highest tuber yield was obtained in the K0 treatment at 2,129 g per treatment. Regression analysis showed a negative relationship between attack intensity and tuber yield with an R² value of 0.6801.